ANALYSIS OF THE IMPACT OF ONLINE LOANS ON USERS FROM AN ISLAMIC ECONOMIC PERSPECTIVE IN MEDAN CITY - Luthfiah Nazmi; Maryam Batubara; Nur Ahmadi Bi Rahmani (Pena Cendekia Insani, 2025)
This study examines the phenomenon of the growing use of online loans in Medan City within the context of the digital economy, viewed from the perspective of Islamic economics. The rapid expansion of application-based lending services has generated various social and economic impacts, particularly in fostering consumerist behavior and creating discrepancies with Islamic financial principles. The objectives of this research are: (1) to identify the factors that drive people to use online loans, (2) to analyze the economic and social effects arising from their use, and (3) to evaluate the conformity of online lending practices with the principles of Islamic economics. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, non-participant observations, and documentation involving 6-10 users of online lending services in Medan City. Data analysis was conducted inductively by interpreting the meanings and experiences of users in light of maq??id al-syari’ah principles. The results reveal that easy access, fast processes, and urgent financial needs are the main factors encouraging people to use online loans. However, high interest rates, late payment penalties, and unethical debt collection methods have caused significant economic and social pressures. From the perspective of Islamic economics, such practices contain elements of riba (usury), gharar (uncertainty), and zulm (injustice), which contradict the Islamic values of fairness, balance, and blessing. This study contributes empirically to strengthening Islamic financial literacy and encourages the development of fintech regulations that align with Islamic ethical values.